Pengembangan Sistem Informasi Musyawarah Dengan Metode Iteratif (Studi Kasus : Masjid Ibnu Sina Jl. Veteran, Malang) - Rizky Novriansyah; Ismiarta Aknuranda; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Ibnu Sina is one of the mosques that has Takmir and Remaja Masjid to revive and carry out the function of the mosque as a place for Muslims to pray. With many activities held by mosques, Takmir and Remaja Masjid often conduct meeting activities to maximize the worship activities to serve people. However, there are problems that occur when conducting meeting and control all of the mosque work. Often times meeting are forgotten and it is difficult to review a certain information from the media stored by takmir mosques, it is books and social media. This has hampered the determination of the decisions that had been agreed. Thus causing multi-perception for each member of the deliberation on the decisions given. This study aims to build an information system that can help manage meeting information. In its development, this system was built using the Java Spring Boot to facilitate development by applying the principle of the module to the feature. The system development method used in this study is an iterative method. Then the system is tested using validation methods and compatibility testing methods. The result of the testing validation is valid and the system can access with any browser.